Ardaman Singh (Farmer) - Ladiankalan, Punjab India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Ardaman Singh is an experienced Indian farmer who have been cultivating for 35 years. He talks about the problems posed by the erratic rainfall and changed temperatures and how they are trying to compensate their income by growing vegetables and fodder in additon to the traditional crops. The villagers have also adapted through including rice varieties who have shorter growing periods and use less water. This has proven to be really beneficial for the farmers.